A Patient Dose-Reduction Technique for Neuroendovascular Image-Guided Interventions: Image-Quality Comparison Study - Sonig, A.; Setlur Nagesh, S.V.; Fennell, V.S.; Gandhi, S.; Rangel-Castilla, L.; Ionita, C.N.; Snyder, K.V.; Hopkins, L.N.; Bednarek, D.R.; Rudin, S.; Siddiqui, A.H.; Levy, E.I. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: The ROI–dose-reduced intervention technique represents an extension of ROI fluoroscopy combining x-ray entrance skin dose reduction with spatially different recursive temporal filtering to reduce excessive image noise in the dose-reduced periphery in real-time. The aim of our study was to compare the image quality of simulated neurointerventions with regular and reduced radiation doses using a standard flat panel detector system.MATERIALS AND METHODS: Ten 3D-printed intracranial aneurysm models were generated on the basis of a single patient vasculature derived from intracranial DSA and CTA. The incident dose to each model was reduced using a 0.7-mm-thick copper attenuator with a circular ROI hole (10-mm diameter) in the middle mounted inside the Infinix C-arm. Each model was treated twice with a primary coiling intervention using ROI-dose-reduced intervention and regular-dose intervention protocols. Eighty images acquired at various intervention stages were shown twice to 2 neurointerventionalists who independently scored imaging qualities (visibility of aneurysm-parent vessel morphology, associated vessels, and/or devices used). Dose-reduction measurements were performed using an ionization chamber.RESULTS: A total integral dose reduction of 62% per frame was achieved. The mean scores for regular-dose intervention and ROI dose-reduced intervention images did not differ significantly, suggesting similar image quality. Overall intrarater agreement for all scored criteria was substantial (Kendall τ = 0.62887; P < .001). Overall interrater agreement for all criteria was fair (κ = 0.2816; 95% CI, 0.2060–0.3571).CONCLUSIONS: Substantial dose reduction (62%) with a live peripheral image was achieved without compromising feature visibility during neuroendovascular interventions.DRIdose-reduced interventionRDIregular-dose intervention